Apprenticeships in education and the differences – resistance to the cultural heteroterrorism: that only the kisses cap the mouth (Research, Society and Development, 2020)
The present article aims to discuss other models of thinking apprenticeships in the education starting from the crossings provoked by the trans bodies in different practices and educative territories. The question that leads the debate is: how the existences (or the resistances) of the trans bodies challenge the normalizer education in the production of learnings by the differences? To do so, the Sociopoetic’s methodology passes over the text, potentializing the affective and artistic dimensions of the trans bodies, by the means of the narratives and graffiti of the young trans woman and, also, conffection (concepts + affection) produced by the trans women educators. As result, it found that diversity discourses and tolerance are not thought to the trans bodies, but about these. In this sense, such speeches are only static representation of the differences. The education is part of an game that produces differences, however, sometimes, standards the bodies in a binary order of genders, imposing countless ways of violence characterized as cultural heteroterrorism. In spite of that, the several skins of the young trans woman and the experiences of the trans women educators bring on the thought about diversity through encounters with the differences, a chaotic movement that destabilize the normative truths which rule the education. It concludes that the education must blot the edges between the bodies, making to emerge the multiplicity of senses; to learn with the differences it is to exercise the art of the meetings, as a kiss, to educate is done in the encounters.